HUBUNGAN ANTARA MINAT DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR DITINJAU DARI INPUT MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN FKIP UNS - Latifah, Nur Umi (Jurnal Nosel, 2016)
The purpose of this research is to know the correlation between interests and motivation with learning achievement observed from student input (Senior High School and Vocational High School) in Study Program of Mechanical Engineering Education Faculty of Teacher Training and Education Sebelas Maret University the generation 2012 and 2013. Types of this research is quantitative research that uses descriptive and cross-sectional as correlational analytic. The population of this research are student in the generation 2012 and 2013. The amounted of student is 133. The research sample are 100 students consist of 52 students in the generation 2012 and 48 students in the generation 2013, the sample is taken by simple random sampling out of the 69 students in the generation 2012 and 64 students in the generation 2013. The data collected by questionaire and documentation. The techniques of data analyz conducted by used simple linier regression test and multiple linier regression test using SPSS version 17.0. The data analyzed by normalitas test, multikolinieritas test dan linieritas test. The result of the statistic multiple linier regression test showed that:Student (1) There is a significant positive relations between interests and motivation of the learning achievement in theory courses of student input from Senior High School in generation 2012, it is evidenced with the value of Fcount (5,614 ) > Ftable (3,259) and pvalue = 0,008 (p value < 0,05); (2) There is no correlation between interests and motivation with learning achievement in practice course of student input from Senior High School in generation 2012, it is evidenced with the value of Fcount (2,344) < Ftable (3,259) and pvalue = 0,110 (pvalue > 0,05); (3) There is a significant positive correlation between interests and motivation with learning achievement in theory course of student input from Vocational High School in generation 2012, it is evidenced with the value of Fcount (6,281) > Ftable (4,103) and pvalue = 0,017 (pvalue < 0,05); (4) There is a significant positive correlation between interests and motivation with learning achievement in practice course of student input from Vocational High School in generation 2012, it is evidenced with the value of Fcount (7,486) > Ftable (4,103) and p value = 0,010 (pvalue < 0,05); (5) There is a significant positive correlation between interests and motivation with learning achievement in theory course of student input from Senior High School in the generation 2013, it is evidenced with the value of Fcount (14,481) > Ftable (3,443) and pvalue = 0,000 (pvalue < 0,05); (6) There is a significant positive correlation between interests and motivation with learning achievement in practice course of student input from Senior High School in generation 2013, it is evidenced with the value of Fcount (5,002) > Ftable (3,443) and pvalue = 0,016 (pvalue < 0,05); (7) There is a significant positive correlation between interests and motivation with learning achievement in theory course of student input from Vocational High School in generation 2013, it is evidenced with the value of Fcount (4,925) > Ftable (3,493) and pvalue = 0,018 (pvalue < 0,05); (8) There is no correlation between interests and motivation with lea rning achievement in practice course of student input from Vocational High School in generation 2013, it is evidenced with the value of Fcount (3,317) < Ftable (3,493) dan p value = 0,057 (pvalue > 0,05). The conclusion from the research result showed that the interest and motivation with learning achievement in the theory courses have the significant effect with the student input both Senior High School and Vocational High School. Otherwise, that should not too influence with the practice courses. Based on this conclusion shows that the high interest and motivation at the same time will increase the learning achievement in the same time will increase, then to improve learning achievement should be the lecturer foster the interest and motivation of students, thus there are expected to improve the learning achievement both theory and practice cours.